2017
DOI: 10.1038/ncb3594
|View full text |Cite
|
Sign up to set email alerts
|

SMC complexes differentially compact mitotic chromosomes according to genomic context

Abstract: Structural Maintenance of Chromosomes (SMC) protein complexes are key determinants of chromosome conformation. Using Hi-C and polymer modeling, we study how cohesin and condensin, two deeply conserved SMC complexes, organize chromosomes in the budding yeast Saccharomyces cerevisiae. The canonical role of cohesin is to co-align sister chromatids whilst condensin generally compacts mitotic chromosomes. We find strikingly different roles for the two complexes in budding yeast mitosis. First, cohesin is responsibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
165
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(186 citation statements)
references
References 67 publications
20
165
1
Order By: Relevance
“…Optical imaging can also capture chromosome dynamics and 3D positioning of loci in live cells, neither of which can be determined using static Hi‐C data from large heterogeneous populations of cells. However, recent Hi‐C analysis of single cells or populations of mouse and yeast cells with known positions in the cell cycle has documented stage‐specific differences in chromosome conformation . The next challenge in this area is to describe the 4D changes in chromosome structure and dynamics in living cells progressing through an unperturbed cell cycle.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical imaging can also capture chromosome dynamics and 3D positioning of loci in live cells, neither of which can be determined using static Hi‐C data from large heterogeneous populations of cells. However, recent Hi‐C analysis of single cells or populations of mouse and yeast cells with known positions in the cell cycle has documented stage‐specific differences in chromosome conformation . The next challenge in this area is to describe the 4D changes in chromosome structure and dynamics in living cells progressing through an unperturbed cell cycle.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, recent Hi-C analysis of single cells or populations of mouse and yeast cells with known positions in the cell cycle has documented stagespecific differences in chromosome conformation. [151][152][153][154] The next challenge in this area is to describe the 4D changes in chromosome structure and dynamics in living cells progressing through an unperturbed cell cycle. All of these efforts will be advanced by the development of new imaging instrumentation and experimental tools that will achieve higher resolution and higher content imaging of live single cells.…”
Section: Biological Questionsmentioning
confidence: 99%
“…Sister chromatid cohesion is mediated by cohesin complexes which maintain replicated chromatids in proximity 9 . Recent studies have shown that cohesins also tether loci in cis thus folding individual chromatids into distinct loops that provide an integral level of genome architecture [3][4][5] . The current favoured model for how these cohesin-dependent loops are formed on chromosomes involves their dynamic extension through cohesin rings 3 , also referred to as loop extrusion 10 .…”
Section: Mainmentioning
confidence: 99%
“…3a-c), we sought to investigate the functional consequences for chromosome architecture. Cohesin holds sister chromatid together 1,2 and organises intra-chromatid loops that provide an integral level of structure to chromosomes 4,5 . First, we tested whether cohesion between sister chromatids is affected in G2/M arrested cells when Spt16 is depleted.…”
Section: Mainmentioning
confidence: 99%
“…It will be of great interest to analyze them, for instance, by recently developed electron microscopy (EM) tomography, known as ChromEMT (Ou et al 2017). There is no doubt that genome-based approaches such as Hi-C techniques (Naumova et al 2013;Kakui et al 2017;Lazar-Stefanita et al 2017;Schalbetter et al 2017) and mechanical stretching approaches (Almagro et al 2004;Yan et al 2007;Xiao et al 2012) will also provide valuable information regarding the architecture and physical properties of the in vitro assembled chromosomes. Powerful combinations of the sophisticated in vitro assays and the emerging analytical technologies will provide us with a key to unlock one of the most important questions in biology: How is a centimeters-long genomic DNA folded into a micrometers-long chromosome?…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%